What's in a name? Role of verbal context in touch - Supreet Saluja; Karina Chan; Tully Lynch; Richard J. Stevenson (Royal Society Open Science, 2022)
Can a name (i.e. verbal context) change how we react to and perceive an object? This question has been addressed several times for chemosensory objects, but appears unanswered for touch. To address this, two studies were run. In each, we allocated participants to a Positive, Neutral or Negative Group, and asked them to touch the same four objects, twice—first, named by the experimenter according to their Group-name, and second, named by the participant. Participants were timed as they touched and rated the objects on pleasantness and disgust. Negative-named objects were touched for shorter durations, and rated more negatively, than neutral-named objects, and positive-named objects were touched for the longest and rated most positively. In the second presentation, most objects (greater than 90%) were named by participants in accordance with their assigned Group-names. The similarity of these findings to chemosensory verbal context effects and their mechanistic basis is discussed.